Feeding Behaviors of Children with Autism Spectrum Disorder in Baghdad City - Ali, Ahmed; Ghanim, Eqbal (Iraqi National Journal of Nursing Specialties, 2020)
Objective(s): To assess the behavior that impedes the eating of children with autism spectrum disorders in Baghdad city, and find out the relationships between the behaviors that impede eating of autistic children and their demographic characteristics.Methodology: The study started from the period of 16th September 2019 to the 16th of March 2020. A non-probability (purposive) sample of 80 children with autism spectrum disorders was selected. The questionnaire was designed and composed of two parts: the first part includes the autistic children demographic data, the second part includes scales of behavior that impede eating followed by parents towards autistic child. The reliability of the questionnaire was determined through a pilot study and the validity through a panel of (14) experts. The data were collected by questionnaire. The data were described statistically and analyzed through the use of descriptive and inferential statistical analysis procedures.Results: The results of the present study indicated that feeding behaviors of autistic children were affected at moderate level, with respect to the relation of autistic children socio-demographic data with their feeding behaviors levels, no significant association was determined.Recommendations: The study recommended that those children need for special rehabilitative and behavioral programs dealing with their behavioral problems, and to improve their feeding behaviors.